Notary Role In The Bonding Object To The Settlement Of Liability Rights In Banking Credit Loss (Case Study In Semarang) - Arya Fathurahman; Sulistyo Utomo; Amin Purnawan; Setyawati Setyawati (Jurnal Akta, 2019)
The purpose of this study was to: 1) To Assess and analyze the role of the Notary in binding Collateral Object Encumbrance against Settlement Bad Debt in the city, 2) to Review and Analyze Effects, Barriers and Solutions in fastening places Encumbrance if not done before Notary , The method used in this study using a normative legal research legal research conducted by reviewing the materials are derived from legislation and other materials from a variety of literature.Based on the results of data analysis concluded that: 1) the importance of the role of the Notary that leads to Article 15 (1) UUHT determine that importance a strand Attorney Imposing Mortgage (SKMHT) shall be made by notarial deed or deed of PPAT. 2) The legal consequences for binding Binding Objects Encumbrance if not done in the presence of a Notary (1) agreements that do lose their authenticity as stated in Article 16 paragraph (8) UUJN, (2) the lender does not get a position that takes precedence (droit de preference), (3) in the event of default, the guarantee can not be directly executed, (4) proof of the deed made does not apply to third parties, so that the settlement be reached only through a settlement amicably, (5) affects the motivation of members financing to meet with a good performance. As for barriers and solutions if agreement encumbrance not done before Notary can be divided into three, namely: (1) prior to binding, associated with the filing requirements of the binding as of the identity of the parties, the object of the guarantee, and is authorized to act by the parties, (2) binding collateral, related to the change in attitude of the debtor and the binding process at the local BPN (3) after the binding, associated with the increase of SKMHT be APHT and roya against collateral.Keywords: Role of the Notary; Binding Objects Mortgage; Bad Debt.